Pengaruh lingkungan sosial terhadap strategi dakwah IPNU-IPPNU dalam mengatasi kenakalan remaja di Kecamatan Banyakan Kediri - Ulum, Ilsa Fikrotul (Maliki Interdisciplinary Journal, 2025)
The influence of the social environment has a tremendous influence on the lives of today’s young people. Life became sophisticated with the evolution of civilization from primitive conditions to complete technology. These influences affect human life, especially young people. In Kaligaya hamlet, the IPNU-IPPNU organization has a good strategy for dealing with young people and reducing acts of juvenile delinquency. Nowadays there is a lot of juvenile delinquency which is very detrimental, one of which is drinking alcohol, smoking, theft, these are all mischief committed by young people. This research aims to provide information and inspiration to young people, and strategies on how to prevent juvenile delinquency. This research uses a qualitative descriptive research type. Using the literature review method, by providing an overview of the phenomenon using the SWOT analysis approach method. The ipnu-ippnu organization in the community can bring the best solution to overcome this problem. From the discussion it can be concluded that ipnu-ipnn has a strategy to prevent juvenile delinquency, especially in Kaligayam village, including: Strength, Weakness, Opportunity and Threats. The strategy variants applied by the organization for students are: motivation, organizing, competitions, protecting differences and implementing religious education.